Megaduodenum in a 59-year-old man: a very late postoperative complication after duodenal atresia. (18th January 2018) - Rueff, Jessica; Söllner, Oliver; Zuber, Markus; Weixler, Benjamin
Abstract : Intestinal malformations are common defects of the newborn, treated in experienced centres. Reports on long-term follow-up and associated complications are scarce, possibly leading to misinterpretation of clinical signs and symptoms in adulthood. To prevent treatment errors, it is important that physicians are aware of long-term complications of intestinal malformations.